2019
DOI: 10.1371/journal.pone.0226644
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cardiovascular diseases related admissions in a referral hospital in the South West region of Cameroon: A cross-sectional study in sub-Saharan Africa

Abstract: BackgroundSub-Saharan Africa (SSA) is experiencing an epidemic of cardiovascular diseases (CVD) as a result of a rapid epidemiological transition. Little is known about the admission for CVD and outcome in rural and semi-urban settings in Cameroon in this era of epidemiological transition. The aim of this study was to determine the frequency and the pattern of CVD admissions in the South West region of Cameroon.MethodsThis retrospective descriptive study included all adult patients admitted for CVD in the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
4
8
0
Order By: Relevance
“…More females than males were hospitalized for CVDs within the study period. Similar observation was reported by Adedapo 15 , Oguanobi et al 40 , Njoku et al 14 , Nwafor et al 29 and Nkoke et al 16 in Ibadan, Enugu, Keffi, Portharcourt and Southwest Cameroun respectively but contradicts those of some other researchers from within Nigeria 26,28 . This could be because the present study spanned over 10 years with more participants than the other studies which were for a period of 2-3 years with fewer study populations.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…More females than males were hospitalized for CVDs within the study period. Similar observation was reported by Adedapo 15 , Oguanobi et al 40 , Njoku et al 14 , Nwafor et al 29 and Nkoke et al 16 in Ibadan, Enugu, Keffi, Portharcourt and Southwest Cameroun respectively but contradicts those of some other researchers from within Nigeria 26,28 . This could be because the present study spanned over 10 years with more participants than the other studies which were for a period of 2-3 years with fewer study populations.…”
Section: Discussionsupporting
confidence: 79%
“…In a hospital based study in Keffi 14 , Northcentral Nigeria, CVDs were the predominant NCDs causing hospitalization followed by diabetes mellitus (DM) related complications at 37.7% and 23.7% respectively. In another hospital based study in South-western Nigeria 15 , CVDs accounted for 37.0% of all medical admissions with an overall mortality of 17% while in a hospital based study in Southwest Cameroun 16 , CVDs accounted for 15.9% of medical admissions with 15.8% in-hospital case fatality. In a Pakistan 17 cross sectional study, the pattern of NCDs noted were systemic hypertension, ischemic heart diseases and DM at 38.7%, 34.4% and 14.6% respectively with identified risk factors being tobacco use (48.2%), drug abuse (13.6%) and alcohol consumption (1.8%).…”
Section: Introductionmentioning
confidence: 94%
“…Cardiovascular disease (CVD) is a leading cause of death and in sub Saharan Africa; women are more likely to die of heart disease compared to the men. [1,2] Overall, incidence of heart disease and other non-communicable diseases is on the on the rise in resource limited settings. [3] Prior history of pre-eclampsia or eclampsia increases cardiovascular risk later in life.…”
Section: Introductionmentioning
confidence: 99%
“…More than 80% of CDV deaths occur in low and middle-income countries, affecting men and women at the same rates [4]. A recent study carried out in Cameroon showed that deaths related to CDV (in-hospital case-fatality) were 15.8% [5].…”
Section: Introductionmentioning
confidence: 99%